Mechanism of the Reductive Activation of O2 to O22- from a Vanadium(IV) Species and Its Potential Use in Fuel Cells - Keramidas, Anastasios D.; Papanikolaou, Michael G.; Hadjithoma, Sofia; Keramidas, Odysseas; Amoiridis, Aggelos; Drouza, Chryssoula; Themistokleous, Alexandros; Hayes, Sofia C.; Lianos, Panagiotis; Tsipis, Athanassios C.; Kabanos, Themistoklis A. (My University, 2023)
The two electron reductive activation of O2 to O22- is of particular interest to scientific community mainly due to the use of peroxides as green oxidants and in powerful fuel-cells. Among the metal-ions which activate O2, vanadium is of particular interest because of its numerous oxidative catalytic properties. Reaction of either VIVOSO4.3.5H2O or VIVOCl2 with N-(8-quinolyl)pyridine-2-carboxamide (Hpbq) in CH3OH solution under atmospheric O2, at room temperature, resulted in the quick formation of [VVO(k2-O2)(pbq)(H2O)](1). Compound 1 constitutes a rare example of formation of a (peroxo)oxidovanadium(V) complex from molecular O2 and an oxidovanadium(IV) complex. The reaction of formation of compound 1vs. time was monitored by 51V and 1H NMR, UV-vis, cw-X-EPR, Resonance Raman spectroscopiesand cyclic voltammetry revealing the formation of a stable radical intermediate [VVO(k2-O2)(pbq)(H2O)]•+. Dynamic experiments in combination with computational calculations were used to elucidate the mechanism of the reaction. The galvanic cell {Zn|VIII,VII||cis-[VVO2(bpq)], [VVO(O2)(bpq)(H2O)],[VIVO(bpq)(H2O)2]+|O2|C(s)} was manufactured, demonstrating that this technology can be used in Zn|H2O2 fuel cells generating H2O2 in situ from atmospheric O2.
Keywords: Electron reductive activation; Green oxidants; Powerful fuel-cells